Survival and differentiation of dopaminergic mesencephalic neurons are promoted by dopamine-mediated induction of FGF-2 in striatal astroglial cells - Reuss, Bernhard; Unsicker, Klaus (Molecular and cellular neuroscience, 2002)
Survival of dopaminergic (DAergic) midbrain neurons during development and after lesioning depends, in part, on the presence of astroglia-derived growth factors, as, e.g., fibroblast growth factor (FGF)-2. Astrocytes express DA receptors in a brain-region-specific manner. We show here that DA (10−3 to 10−6 mol/liter) applied continuously for 12 h or as a 10-min pulse significantly upregulates FGF-2 immunoreactivity quantified by Western blot and densitometry in astrocytes cultured from two target areas of DAergic neurons, striatum and cortex, but not in mesencephalic astroglia. Semiquantitative competitive RT-PCR confirmed the increase in FGF-2 on the mRNA level. The effects were specific in that glutamate, which can also activate receptors on astroglial cells, did not influence FGF-2 synthesis. In addition to the DA-mediated increase in FGF-2 synthesis the capability of conditioned medium (CM) from DA-stimulated striatal and cortical astrocytes to promote survival and process formation of cultured rat DAergic neurons was significantly enhanced. These effects could be fully blocked by preincubation of the CM with an FGF-2-specific polyclonal antiserum. Our results suggest that DA released from DAergic axon terminals in target regions of DAergic neurons and astroglial FGF-2 production are interdependent in that DA triggers synthesis of FGF-2, which, in turn enhances survival and differentiation of DAergic neurons.
Gesehen am 25.11.2016